Investigation of Compressible Electromagnetic Flute Mode Instability in Finite Beta Plasma in Support of Z-Pinch and Laboratory Astrophysics Experiments (Communications in Computational Physics, 2008)
Flute mode turbulence plays an important role in numerous applications,such as tokamak, Z-pinch, space and astrophysical plasmas. In a low beta plasmaflute oscillations are electrostatic and in the nonlinear stage they produce large scaledensity structures co-mingling with short scale oscillations. Large scale structures areresponsible for the enhanced transport across the magnetic field and appearance ofshort scales leads to ion heating, associated with the ion viscosity. In the present papernonlinear equations which describe the nonlinear evolution of the flute modes treatedas compressible electromagnetic oscillations in a finite beta inhomogeneous plasmawith nonuniform magnetic field are derived and solved numerically. For this purposethe 2D numerical code FLUTE was developed. Numerical results show that even ina finite beta plasma flute mode instability can develop along with formation of largescale structures co-existing with short scale perturbations in the nonlinear stage.